“Covid-19 and Stock Market Behavior – An Event Study of BRIC Countries” - Dr. Kanika Sachdeva, Dr. P. Sivakumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The purpose of this research is to estimate the influence of COVID-19 epidemic on the behavior of stock markets in BRIC nations. The effects of infectious disease are important, and they have had a direct effect on financial markets around the world. Our sample is made up of BRIC country indices. The market model event methodology approach was used to conduct the analysis. The event window is considered as 72 days after the announcement of Novel COVID-19 as human transmitted disease in the global press, and estimation window is considered as -150 days from the occurrence of the event date. During the 72-day event window, six sub-event windows have recorded negative CARs. According to the results of this report, from day 0 to day 60 the cumulative average abnormal return (hereafter referred as CAAR) ranges between –0.85 % to –7.28 %, which is result of amplified stress in the financial markets caused by a rise in the counts of COVID-19 infected cases in BRIC nations. CAAR ranges between –7.28 % to –0.10 % from day 60 to day 72 suggests stock market recovery following a significant correction in the closing prices of indices among the selected nations due to COVID-19.